2020
DOI: 10.2147/dmso.s281949
|View full text |Cite
|
Sign up to set email alerts
|

<p>Type 1 Diabetes Mellitus in Pediatric Patients and Its Impact on Relationships in the Family Environment</p>

Abstract: Purpose The aim of this study is to assess the impact of type 1 diabetes mellitus on family environment relationships, as well as the management and approach to this disease. Patients and Methods One hundred one children, 52.47% male and 47.52% female, with an average age of 8.55 ± 4.01 years, diagnosis of type 1 diabetes mellitus. Quantitative cross-sectional descriptive study was conducted using the validated questionnaires “Modified Diabetes Quality of Life” and “Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Others concluded that an accurate analysis and effective intervention must take into account the children's emotions to increase glycemic balance [35]. On the other hand, caregivers must receive the necessary support and tools to manage crisis situations [36].…”
Section: Discussionmentioning
confidence: 99%
“…Others concluded that an accurate analysis and effective intervention must take into account the children's emotions to increase glycemic balance [35]. On the other hand, caregivers must receive the necessary support and tools to manage crisis situations [36].…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 diabetes mellitus (T1DM), an immune-mediated condition, is one of the most common chronic diseases in children [1]. It culminates in the complete or partial loss of pancreatic β cells, leading to reduced production of endogenous insulin and necessitating exogenous insulin administration to sustain proper energy production [2].…”
Section: Introductionmentioning
confidence: 99%